Diagnostic stewardship for blood cultures in the pediatric intensive care unit: lessons in implementation from the BrighT STAR Collaborative - Charlotte Z. Woods-Hill; Danielle W. Koontz; Anping Xie; Elizabeth A. Colantuoni; Anna Sick-Samuels; Marlene R. Miller; Abigail Arthur; Anushree Aneja; Urmi Kumar; Aaron M. Milstone; for the Brigh T STAR authorship group (Cambridge University Press, 2024)
Abstract Objective: BrighT STAR was a diagnostic stewardship collaborative of 14 pediatric intensive care units (PICUs) across the United States designed to standardize and reduce unnecessary blood cultures and study the impact on patient outcomes and broad-spectrum antibiotic use. We now examine the implementation process in detail to understand how sites facilitated this diagnostic stewardship program in their PICUs. Design: A multi-center electronic survey of the 14 BrighT STAR sites, based on qualitative data about the implementation process collected during the primary phase of BrighT STAR. Setting: 14 PICUs enrolled in BrighT STAR. Participants: Site leads at each enrolled site. Methods: An electronic survey guided by implementation science literature and based on data collected during BrighT STAR was administered to all 14 sites after completion of the primary phase of the collaborative. Results: 10 specific tasks appear critical to implementing blood culture diagnostic stewardship, with variability in site-level strategies employed to accomplish those tasks. Sites rated certain tasks and strategies as highly important. Strategies used in top-performing sites were distinct from those used in lower-performing sites. Certain strategies may link to drivers of culture overuse and represent key targets for changing clinician behavior. Conclusions: BrighT STAR offers important insights into the tasks and strategies used to facilitate successful diagnostic stewardship in the PICU. More work is needed to compare specific strategies and optimize stewardship outcomes in this complex environment. Clinical trial registry information: Blood Culture Improvement Guidelines and Diagnostic Stewardship for Antibiotic Reduction in Critically Ill Children (Bright STAR). NCT03441126. https://www.clinicaltrials.gov/study/NCT03441126?term=Bright%20STAR&aggFilters=status:com&checkSpell=false&rank=1